Buoyancy, salt tolerance and germination of coastal seeds: implications for oceanic hydrochorous dispersal - Guja, Lydia; Merritt, D.; Dixon, K. (CSIRO Publishing, 2010)
Many coastal plant species are widely distributed, including several pan-global species. Long-distance dispersal and physiological resilience of diaspores (i.e. the plant dispersal unit encompassing the seed and any additional surrounding or attached tissues at dispersal) to adverse environmental conditions are possible contributors to the presence of species over hundreds of kilometres of coastline. Dispersal by water (hydrochory) may occur in coastal habitats. This study investigated diaspore traits considered important for oceanic hydrochorous dispersal, including morphology, buoyancy and survival in seawater, and germination under saline conditions for 13 species common to Holocene dune communities in Western Australia. Of the diaspores of 13 species dominant in this coastal community, 11 floated in seawater, with 7 having >50% of diaspores buoyant after 14 days and some diaspores remaining buoyant for 70 days. Of the 10 species that germinated, diaspores of 9 survived exposure to seawater for up to 70 days.Germination of physiologically dormant seeds contained within indehiscent woody fruits and physically dormant seeds was least affected by time in seawater. The effects of varying concentrations of NaCl (0–500 mM) on germination differed between species, but most were able to recover and germinate when transferred to non-saline water. Three different patterns of salt response were observed. It appears likely a combination of diaspore traits, rather than a single factor, facilitate oceanic hydrochorous dispersal.